Numerical Computation of Turbulent Flow and Heat Transfer in a Radially Rotating Channel with Wall Conduction - Frank K. T. Lin; G. J. Hwang; S.-C. Wong; C. Y. Soong (International Journal of Rotating Machinery)
This work is concerned with numerical computation of turbulent flow and heat transfer in experimental models of a radially rotating channel used for turbine blade cooling. Reynolds-averaged Navier-Stokes and energy equations with a two-layer turbulence model are employed as the computational model of the flow and temperature fields. The computations are carried out by the software package of “CFX-TASCflow”. Heat loss from the channel walls through heat conduction is considered. Results at various rotational conditions are obtained and compared with the baseline stationary cases. The influences of the channel rotation, through-flow, wall conduction and the channel extension on flow and heat transfer characteristics are explored. Comparisons of the present predictions and available experimental data are also presented.